Resposta:
Alternativa c)
Explicação passo a passo:
[tex]\displaystyle y=\frac{(-5)^2-4^2+(\frac{1}{5})^0 }{3^{-2}+1} =\frac{25-16+1 }{(\frac{1}{3})^2+1} =\frac{10}{(\frac{1}{9})+1} =\frac{10}{\frac{1+9}{9}} =\frac{10}{\frac{10}{9}} =10.\frac{9}{10} =9[/tex]
C)y=9
Resolva a potencia
[tex](-5)^{2} -4^{2} +(\frac{1}{5} )^{0}[/tex]
[tex]\frac{}{3^{2} +1}[/tex]
Calcule
[tex]\frac{25-16+1}{\\} \\ \frac{1}{3^{2} } +1[/tex]
[tex]\frac{10}{1} \\\frac{}{9} +1[/tex]
simplifique
[tex]\frac{10}{10}\\\frac{}{9}[/tex]
Copyright © 2025 ELIBRARY.TIPS - All rights reserved.
Lista de comentários
Verified answer
Resposta:
Alternativa c)
Explicação passo a passo:
[tex]\displaystyle y=\frac{(-5)^2-4^2+(\frac{1}{5})^0 }{3^{-2}+1} =\frac{25-16+1 }{(\frac{1}{3})^2+1} =\frac{10}{(\frac{1}{9})+1} =\frac{10}{\frac{1+9}{9}} =\frac{10}{\frac{10}{9}} =10.\frac{9}{10} =9[/tex]
Resposta:
C)y=9
Explicação passo a passo:
Resolva a potencia
[tex](-5)^{2} -4^{2} +(\frac{1}{5} )^{0}[/tex]
[tex]\frac{}{3^{2} +1}[/tex]
Calcule
[tex]\frac{25-16+1}{\\} \\ \frac{1}{3^{2} } +1[/tex]
Calcule
[tex]\frac{10}{1} \\\frac{}{9} +1[/tex]
simplifique
[tex]\frac{10}{10}\\\frac{}{9}[/tex]